Sports services management using assessment tools: net promoter score and importance-performance analysis - Gálvez Ruiz, Pablo; Lara-Bocanegra, Alejandro; García Fernández, Jerónimo; Núñez-Sánchez, José Manuel (Cambridge University Press, 2025)
The evaluation of services has become a common strategy in service management, and there is a wide variety of tools available. The objective was to evaluate user satisfaction at a sports center using the Net Promoter Score (NPS) and Importance-Performance Analysis (IPA) techniques, comparing the information provided by each. To this end, this study involved 1,433 users of a sports center, analyzing the responses to the NPS® tool and subsequently to the IPA tool developed ad hoc with 11 attributes. The NPS® tool revealed 29.58% detractors, 30.36% passives, and 40.06% promoters, highlighting a negative impact on the overall score. The IPA tool offered detailed insights into attributes varying across the three NPS groups, identifying four critical attributes requiring strategic attention, enabling segmented marketing strategies. This research demonstrates the complementary value of combining NPS and IPA tools for strategic service management, providing actionable insights to enhance customer satisfaction and competitive positioning.
Keywords: Deportes - Gestión; Servicio al cliente; Satisfacción del cliente; Fitness industry; Sports services management; Net promoter score; Importance performance analysis; Fitness industry; Customer experience